solve the following system of equations

2 (sqrt x) + 5y=16
6 (sqrt x) - 3y=12

1 answer

We can start by solving the second equation for x:

6(sqrt x) - 3y = 12
sqrt x = (12 + 3y)/6
sqrt x = (4 + y)/2

Now we can substitute this expression for sqrt x into the first equation:

2(sqrt x) + 5y = 16
2((4 + y)/2) + 5y = 16
4 + y + 5y = 16
6y + 4 = 16
6y = 12
y = 2

Now we can substitute y = 2 back into either equation to solve for x:

2(sqrt x) + 5(2) = 16
2(sqrt x) + 10 = 16
2(sqrt x) = 6
sqrt x = 3
x = 9

So the solution to the system of equations is x = 9 and y = 2.